2021
DOI: 10.1186/s13048-021-00887-w
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node identification in early stage ovarian cancer: is it still possible after prior tumor resection?

Abstract: Objective Sentinel lymph node (SLN) detection in ovarian cancer is feasible when tracers are injected before the pathological ovary is resected. This study aims to investigate whether the SLN identification is also feasible in patients whose ovarian tumor has already been resected with injection of the tracer into the ovarian ligaments stumps, i.e. in the event that a frozen section confirms malignancy. Methods Patients who underwent laparotomy wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…A number of three studies by Lago et al ( 10 , 11 ) and Laven et al ( 12 ) considered an overall total of 41 patients with tracer injection after ovarian mass resection during the same or a subsequent surgical procedure. In other words, the patients underwent laparotomy with frozen section for a pelvic mass suspicious for malignancy or a second staging laparotomy after prior resection of a malignant ovarian mass.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of three studies by Lago et al ( 10 , 11 ) and Laven et al ( 12 ) considered an overall total of 41 patients with tracer injection after ovarian mass resection during the same or a subsequent surgical procedure. In other words, the patients underwent laparotomy with frozen section for a pelvic mass suspicious for malignancy or a second staging laparotomy after prior resection of a malignant ovarian mass.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, the reliability could be lower due to alteration of the lymphatic drainage after ovarian mass resection. Laven et al ( 12 ) reported that “SLN procedure after (previous) resection of the tumor seems inferior to detect sentinel nodes when compared to injection of the tracer in the ovarian ligaments before tumor resection.” However, SLN detection rates were 100% in the Lago et al’s studies ( 10 , 11 ). As such, overall, detection rate for these cases (with the injection site in the ligament stumps) was 59% [95% CI: 32–81].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A clinical study of early-stage epithelial ovarian cancer found a higher positive rate (88.9 vs. 41.7%) for immediate surgical staging than for delayed surgical staging ( 25 ). Results of another clinical trial of early-stage ovarian cancer showed that if SLN mapping was postponed until 5–8 weeks after tumor resection, SLN mapping would not be successfully localized ( 26 ).…”
Section: Introduction To Sentinel Lymph Node Techniquesmentioning
confidence: 99%